Dietary Oil from Hermetia illucens L. Larvae Promotes Weight Gain and Alters Leukocyte Profiles in Mus musculus L - Nugroho, Rudy Agung, RAN; Kurniati, Reni; Sari, Widya Putri Ambar; Sompotan, Reynaldo Imanuel; Aryani, Retno; Manurung, Hetty; Rudianto, Rudianto (UI Scholars Hub, 2026)
The escalating global demand for high-quality animal-derived proteins has driven the search for sustainable alternatives. Black soldier fly larvae (BSFL; Hermetia illucens L.) oil presents a promising option, by addressing organic waste management while providing nutrient-rich feed. This study evaluated the effects of dietary supplementation with BSFL oil on growth performance, hematological characteristics, and blood lipid profiles in mice (Mus musculus). Male mice were randomly assigned to five groups (n = 5): positive control (fish oil, 5 mL/kg body weight [BW]), negative control (Aquadest, 5 mL/kg BW), and three treatment groups receiving BSFL oil at 2.5, 5, and 10 mL/kg BW, respectively. Interventions were administered orally for 28 days; assessments included BW, hematological parameters, and lipid profiles. The results indicated that 10 mL/kg BW BSFL oil significantly increased BW (34.40 ± 0.74 g) compared to the fish oil group (31.6 ± 0.67 g, p < 0.05). Hematological parameters and lipid profiles did not differ significantly across groups (p > 0.05). However, leukocyte profiles exhibited significant variations (p < 0.05), particularly at 10 mL/kg BW of BSFL oil, suggesting immunomodulation. This preliminary proof-of-concept study in mice provides the first head-to-head comparison of unrefined BSFL and commercial fish oil utility, offering mechanistic insights applicable to livestock nutrition